2018
DOI: 10.1111/ejn.14123
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine self‐administration is increased after frontal traumatic brain injury and associated with neuroinflammation

Abstract: Traumatic brain injury (TBI) has been linked to the development of numerous psychiatric diseases, including substance use disorder. However, it can be difficult to ascertain from clinical data whether the TBI is cause or consequence of increased addiction vulnerability. Surprisingly few studies have taken advantage of animal models to investigate the causal nature of this relationship. In terms of a plausible neurobiological mechanism through which TBI could magnify the risk of substance dependence, numerous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…These drugs have dramatically different mechanisms of action; alcohol is a positive modulator of GABA A receptors, an antagonist of NMDA glutamate receptors, and has actions at several ion channels, while oxycodone primarily functions as a mu opioid receptor agonist (Cui & Koob, ; Yaksh & Wallace, ). These increases were also observed in both single and repeated blast exposure models of mTBI (i.e., single in (Lim et al ., ), repeated in the present study), consistent with other preclinical studies finding elevated intake of drugs of abuse using different models of TBI (Mayeux et al ., ; Weil et al ., ; Merkel et al ., ; Vonder Haar et al ., ). It should be noted that in our studies using cocaine and oxycodone ((Muelbl et al ., ) and the present study), food self‐administration was conducted prior to drug self‐administration.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These drugs have dramatically different mechanisms of action; alcohol is a positive modulator of GABA A receptors, an antagonist of NMDA glutamate receptors, and has actions at several ion channels, while oxycodone primarily functions as a mu opioid receptor agonist (Cui & Koob, ; Yaksh & Wallace, ). These increases were also observed in both single and repeated blast exposure models of mTBI (i.e., single in (Lim et al ., ), repeated in the present study), consistent with other preclinical studies finding elevated intake of drugs of abuse using different models of TBI (Mayeux et al ., ; Weil et al ., ; Merkel et al ., ; Vonder Haar et al ., ). It should be noted that in our studies using cocaine and oxycodone ((Muelbl et al ., ) and the present study), food self‐administration was conducted prior to drug self‐administration.…”
Section: Discussionmentioning
confidence: 97%
“…() using the lateral fluid percussion model found increased levels of glial fibrillary acidic protein (GFAP), CD68, and ionized calcium‐binding adapter molecule 1 (Iba‐1) to indicate increased levels of neuroinflammation, in addition to increased neuronal degradation measured by Fluoro‐Jade. Other studies using different models of TBI have also reported increased levels of neuroinflammatory markers (Lowing et al ., ; Merkel et al ., ; Merkel et al ., ; Vonder Haar et al ., ). Of note, adolescent mice exposed to a controlled cortical impact TBI had higher preference during cocaine‐induced conditioned place preference compared to non‐TBI mice, however administration of dexamethasone, an anti‐inflammatory steroidal compound, normalized the degree of place preference (Merkel et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, compared with sham‐exposed rats, repeated blast traumatic brain injury (TBI)‐exposed rats were more sensitive to oxycodone‐associated cues during reinstatement, suggesting that repeated blast TBI may disrupt the relationship between oxycodone intake and seeking (Nawarawong et al ., ). Inflammation in the frontal cortex may be one underlying mechanism, as suggested by a study using TBI to expose to cocaine self‐administration (Vonder Haar et al ., ). These studies have clear clinical implications given the well‐established increase in risk of substance abuse in those with a history of early life TBI (Cannella et al ., ).…”
Section: Preclinical Modelsmentioning
confidence: 97%
“…Her latest publication in EJN is titled “Cocaine self‐administration is increased after frontal traumatic brain injury and associated with neuroinflammation”, (Vonder Haar et al., ), https://doi.org/10.1111/ejn.14123.…”
mentioning
confidence: 99%